2014
DOI: 10.1371/journal.pone.0089359
|View full text |Cite|
|
Sign up to set email alerts
|

School and Community-Based Interventions for Refugee and Asylum Seeking Children: A Systematic Review

Abstract: BackgroundResearch for effective psychological interventions for refugee and asylum-seeking children has intensified. The need for interventions in environments more easily accessed by children and families is especially relevant for newly arrived populations. This paper reviews the literature on school and community-based interventions aimed at reducing psychological disorders in refugee and asylum-seeking children.Methods and FindingsComprehensive searches were conducted in seven databases and further inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
225
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 348 publications
(231 citation statements)
references
References 60 publications
0
225
0
6
Order By: Relevance
“…Indicated prevention programmes for depression and conduct problems have showed some positive results (Domitrovich & Greenberg, 2000). Empirically validated treatments for children and adolescents differ for various disorders (Chambless & Ollendick, 2001;Jaycox, Kataoka, Stein, Langley, & Wong, 2012;Stein et al, 2003) and for diverse groups of children (Tyrer & Fazel, 2014). Therefore, although there are a number of probably efficacious interventions, there remains the need for evaluating ongoing interventions for children's mental health and to identify sustainable models of service development and delivery.…”
Section: School-based Interventionsmentioning
confidence: 99%
“…Indicated prevention programmes for depression and conduct problems have showed some positive results (Domitrovich & Greenberg, 2000). Empirically validated treatments for children and adolescents differ for various disorders (Chambless & Ollendick, 2001;Jaycox, Kataoka, Stein, Langley, & Wong, 2012;Stein et al, 2003) and for diverse groups of children (Tyrer & Fazel, 2014). Therefore, although there are a number of probably efficacious interventions, there remains the need for evaluating ongoing interventions for children's mental health and to identify sustainable models of service development and delivery.…”
Section: School-based Interventionsmentioning
confidence: 99%
“…This raises the interesting question as to whether working within the school context can specifically assist in peer-related psychological difficulties. A systematic review of studies of schoolbased interventions for refugee children has highlighted the broad range of different mental health interventions that have been used with varying impact on quantitative measures of mental health (Tyrer and Fazel, 2014). The interventions included individual, group and multimodal (those intervening in a number of areas relevant to the children -such as school, family and individual) interventions, although those with the greatest evidence-base were those that treated post-traumatic stress disorder with verbal exposure to the previous events by utilising either cognitive behavioural therapy (CBT) or narrative exposure therapy (NET).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Narrative Therapy (NET; Ruf et al, 2010) acknowledges the narrative tradition common to most refugee cultures and Cognitive Behavioral Therapy (CBT; Hinton et al, 2005) or Trauma-Focused Cognitive-Behavioral Therapy (TF-CBT) was found to be effective (both individual and group interventions) in the treatment of anxiety, PTSD, depression, peer-problems and functional disturbances (Pacione et al, 2013;Slobodin & de Jong, 2015;Tyrer & Fazel, 2014). As brought forward in this study, parents or caretakers exposed to similar traumatic encounters may suffer similar psychological distress that affects the entire family's emotional and physical wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…As brought forward in this study, parents or caretakers exposed to similar traumatic encounters may suffer similar psychological distress that affects the entire family's emotional and physical wellbeing. Thus, comprehensive or multimodal interventions that aim to concurrently address issues of psychological functioning, physical health and ongoing psychological difficulties with refugee students and their families (Tyrer & Fazel, 2014) should also be considered, thereby strengthening intrafamilial coping resources.To this end, within schools, school social workers, staff/teachers, lay therapists or cultural brokers could be trained to promote mental wellbeing by creating a caring and supporting environment and through implementation of preventative and efficacious psychological functioning (Tyrer & Fazel, 2014).…”
Section: Discussionmentioning
confidence: 99%